Pencegahan Talasemia Melalui Upaya Edukasi dan Skrining Talasemia Pada Remaja - Halimah, Halimah; Yan, Loriza Sativa; Renylda, Reta (Jurnal Abdimas Kesehatan (JAK), 2024)
Thalassemia is a congenital blood disorder caused by a deficiency globin chain production. Indonesia is one of the countries with a high frequency of thalassemia carriers. The government estimates that there will continue to be an increase of around 2.500 children/year. Efforts are needed to prevent the occurrence of thalassemia major, which can reduce the quality and welfare of children's lives through the communication of information and education both directly, videos and booklets, which is then followed by screening for the risk of thalassemia in teenagers at SMU Negeri 3 Jambi. This community service activity aims to increase community knowledge through teenagers, as well as identify the risk of thalassemia in teenagers to introduce early prevention of thalassemia and screen for the risk of thalassemia in the nation's next generation of teenagers. Implementing this service includes lectures, discussions, and education through video media and booklets for 60 students at General Senior High School Number 3 Jambi City, followed by routine blood tests to screen for genes carrying thalassemia. Evaluation of adolescent knowledge is known from the pretest and posttest results within three weeks. The Wilcoxon test results showed that KIE could increase the understanding of all teenagers from a pretest average of 32.75 to 79.12 (mean rank of 30.5). It is hoped that the role of teenagers as change agents is to be able to inform the people around them about thalassemia and how to prevent the occurrence of thalassemia in the next generation.